ASSESSING SERVICE EVOLUTION IN PUBLIC HEALTH CLINICS: A CRITICAL REVIEW OF CHALLENGES, TRENDS, AND INSIGHTS - 1-Mana Saleh MohammadAlSwaid, 2-Abajah Mahdi Abdullah Alabbas, 3-Mohammad Jarallah Naji Alkaabi, 4-mohammed ahmedalialmashham, 5-Duayrim Yahya DuayrimAlhareth, 6-Mansour Mahdi Abdullah Al abbas, 7-Abdullah Saleh Al jumhur, 8-Saleh hussainalialyami (Chelonian Research Foundation, 2023)
This critical review examines the evolution of services in public health clinics, focusing on the challenges faced, current trends, and insightful outcomes. Public health clinics play a pivotal role in delivering primary healthcare, preventive services, and health education to diverse populations. However, their evolution is hampered by resource constraints, regulatory hurdles, and the need for equity in healthcare access. Recent trends show a shift towards integrated care, an emphasis on preventive services, the expansion of telehealth, and increased community engagement. Insights from these evolutions suggest improvements in patient outcomes and cost-effectiveness, highlighting the importance of innovative practices and lessons learned. The review concludes by proposing strategies to overcome challenges, including policy reforms and leveraging technology, and speculates on future directions for public health clinics. This comprehensive analysis aims to inform policymakers, healthcare providers, and researchers about the dynamic landscape of public health clinic services and the need for supportive frameworks to facilitate their growth and effectiveness. Keywords: Public Health Clinics, Service Evolution, Healthcare Challenges, Healthcare Trends, Telehealth, Integrated Care, Health Equity, Policy Recommendations, Innovative Practices, Future Outlook